Constitutional aspect of Consumer protection: Comparative Analysis and the Case of Serbiaon - Damnjanović, Aleksa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
In the last few decades, awareness of consumer rights has grown significantly, and consumer law has become a very dynamic area of ​​law. Thus, consumer protection has found a place in the constitutions of various countries. In the first part of the paper, the author provides an overview of constitutional norms on consumer protection in several European constitutions, paying attention not only to the content of these provisions, but also to their place in the constitutional system. In the second part of the paper, the author points out the dilemma of whether consumer rights represent human rights or are primarily program principles. In the same part, the author also points out the connection between consumer protection and other institutes of constitutional law. Finally, the author pays attention to Art. 90 of the Constitution of the Republic of Serbia, which regulates consumer protection. In doing so, the constitutional norm is placed in the context of the state’s reaction to the boycott of retail chains that was organized in the Republic of Serbia at the beginning of 2025.